Lycopene Aggravates Acute Gastric Injury Induced by Ethanol - Chen, Xin; Zhao, Yuechao; Liu, Keying; Li, Zexu; Tan, Xingru; Wang, Yulong; Gao, Na; Liu, Chenming; Fang, Xiaoqi; Wang, Yanlong (Frontiers in Nutrition, 2021)
Lycopene is an important natural red pigment with strong singlet oxygen and peroxide free radical quenching ability. Ethanol directly destroys the epithelial cells of gastric mucosa, causing oxidative damage and inflammation. To evaluate the effect of lycopene on the ethanol induced gastric injury, 112 adult male Kunming mice were randomly divided into normal control, lycopene control, gastric injury control, omeprazole (20mg/kg) positive control, and lycopene experimental groups (at doses of 10, 50, 100, and 150 mg/kg body weight) in this study. The general and pathological evalution, gastric secretion, as well as the levels of antioxidant and inflammatory factors were detected. In lycopene experimental groups, the amount of gastric juice were lower than that in the gastric injury control group; the levels of T-SOD, and the levels of MDA and inflammatory factors (MMP-9 and MCP-1) decreased. However, general and pathological evaluation of gastric tissues revealed that lycopene (especially at high doses) could aggravate acute gastric mucosal injury induced by ethanol. Therefore, lycopene (especially at high doses) aggravates acute gastric mucosal injury caused by ethanol, but this was not due to oxidative stress or inflammatory factors. In lycopene control group, the levels of MTL, T-SOD, and NO increased, but the levels of ALT and AST decreased, indicating that lycopene has a protective effect on the stomach and liver when ethanol wasn’t taken. It reminds us that, when alcohol is consumed in large quantities, consumption of lycopene products should be carefully considered.